Heart failure and late-onset Alzheimer’s disease: A Mendelian randomization study - Arega, Yibeltal; Shao, Yongzhao (Frontiers in Genetics, 2022)
Some of the observational studies suggested that heart failure (HF) is associated with increased risk of late-onset Alzheimer’s disease (AD). On the other hand, a recently published Two-Sample Mendelian Randomization (2SMR) was reported as inconclusive but the estimated odds ratios (ORs) were less than one indicating a potential causal association between genetically predicted HF and lowered risk of AD. Both HF and AD are quite common among seniors and frequently occur together and resulting in a series of severe medical challenges and increased financial burden on healthcare. It is of great medical and financial interest to further investigate the statistical significance of the potential causal associations between HF and AD using large independent cohorts. To fill this important knowledge gap, the present study used the 2SMR method based on summary data from a recently published and very large genome-wide association study (GWAS) for AD on subjects with European ancestry. The 2SMR analysis provided statistically significant evidence of an association with ORs less than one between genetically predicted HF and late-onset AD (Inverse Variance Weighted, OR = 0.752, p = 0.004; MR Egger, OR = 0.546, p = 0.100; Weighted Median, OR = 0.757, p = 0.014). Further investigations of the significant associations between HF and late-onset AD, including specific genes related to the potential protective effect of HF-related medications on cognitive decline, are warranted.